Content Analysis of Dambus Goes Digital on the TikTok Platform as a Learning Medium for Arts, Culture, and Crafts in Elementary Schools (Universitas Pendidikan Indonesia (UPI), 2026)
The development of digital technology has influenced learning practices in elementary schools, particularly through the use of social media as learning media. TikTok, which is commonly associated with entertainment content, has potential to be utilized as a contextual learning medium that aligns with the characteristics of elementary school students. This study aims to analyze the characteristics and educational content of Dambus Goes Digital on the TikTok platform and examine its potential as a learning medium for Arts, Culture, and Crafts (SBdP) in elementary schools. This research employed a qualitative descriptive approach. The research object consisted of Dambus Goes Digital video content uploaded on TikTok, which was analyzed based on audiovisual presentation, cultural messages, and relevance to SBdP learning objectives. Data were collected through observation and digital documentation and analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that Dambus Goes Digital content can be classified into three main categories, namely Playing Dambus, Learning Dambus Together, and Dambus News. These content categories contain elements of musical arts, local cultural values of Bangka Belitung, and audiovisual presentations that are relevant to SBdP learning objectives in elementary schools. The study concludes that social media–based local cultural content has strong potential as an alternative and complementary learning medium, particularly for introducing traditional music and local culture through a digital approach in elementary education.